2021
DOI: 10.1101/2021.07.18.21260731
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Parkinson PACE subtypes and repurposing treatments through integrative analyses of multimodal clinical progression, neuroimaging, genetic, and transcriptomic data

Abstract: The Parkinson's disease (PD) is a heterogeneous neurodegenerative disease, of which the etiological and pathological mechanisms remain unclear to date. PD has been associated with diverse movement dysfunctions and non-motor symptoms (i.e., symptom heterogeneity) and progression patterns of these symptoms differ from patient to patient (i.e., progression heterogeneity). To address these, the present investigation aims at comprehensively considering full progression course of early PDs to identify subtypes, each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 157 publications
(275 reference statements)
1
4
0
Order By: Relevance
“…In the replication study of the PD progression subtype identification, it has been found that the most severe subtype (S3) had distinctive clinical features when compared to the two less severe subtypes (S1 and S2). Moreover, it was observed that there was limited signal in baseline variables to discriminate between the less severe subtypes [22]. These observations are in line with our results, as the performance of our classifier is poor in discriminating between S1 and S2 (0.576 AUROC).…”
Section: Subtype Prediction At Baselinesupporting
confidence: 91%
See 3 more Smart Citations
“…In the replication study of the PD progression subtype identification, it has been found that the most severe subtype (S3) had distinctive clinical features when compared to the two less severe subtypes (S1 and S2). Moreover, it was observed that there was limited signal in baseline variables to discriminate between the less severe subtypes [22]. These observations are in line with our results, as the performance of our classifier is poor in discriminating between S1 and S2 (0.576 AUROC).…”
Section: Subtype Prediction At Baselinesupporting
confidence: 91%
“…The identification of progression subtypes is of extreme importance in order to attempt settling the heterogeneity of PD. Recent research has shown that people with PD can exhibit a variety of progression patterns from diagnosis onwards [5, 8, 19, 20, 22, 24]. The identification of diseasemodifying treatments can be fostered by finer-grained diagnoses and biomarkers identification, pursuing a precision medicine approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in clinical settings, the explicability of model prediction is as important as its accuracy; it will be critical to push for the development of interpretable machine learning models and diagnostic criteria for characterizing their output. 139 In this vein, popular measures such as the Shapley Additive Explanations have been adapted to the subtyping context to characterize better the generated patient clusters 140 or even to discover new clusters. 141 Alongside technical advancements, implementing these models into clinical practice poses several challenges.…”
Section: Discussionmentioning
confidence: 99%